Depression in metallurgical workers - Díaz, Cecilia (2004)
OBJECTIVE: To seek determinant factors in the development of depression clinical picture. MATERIAL AND METHODS: Study by Hamilton’s Scale of a copper metallurgical mining company 158 railroad men and gantry-crane men workers. Twenty-five probable cases of depression were referred for psychiatric evaluation. In 13 diagnosis was confirmed and represent the cases group and the remaining 140 men, the control group. Both groups were compared statistically by logistic regression. Confidence intervals were calculated at 95%. RESULTS: Depression prevalence was 8,49%. Feeling of current loss, family severe dysfunction, improper working conditions and occupational performance represented probability reasons with P value highly meaningful (59,3; 11,4; 10,0; 11,2, respectively). Age, civil state, education level, alcohol or tobacco consumption, personal or familiar history of psychiatric disorder, chronic organic illness were not meaningful. CONCLUSIONS: Depression in the studied workers is strongly associated with feeling of current loss, severe familiar dysfunction, occupational performance and inadequate working conditions, constituting risk factors.